2020
DOI: 10.1002/term.3014
|View full text |Cite
|
Sign up to set email alerts
|

Genipin‐crosslinked decellularized annulus fibrosus hydrogels induces tissue‐specific differentiation of bone mesenchymal stem cells and intervertebral disc regeneration

Abstract: Biomaterial‐based therapy that can restore annulus fibrosus (AF) function in early stage and promote endogenous repair of AF tissues is a promising approach for AF tissue repair. In this study, we established a genipin‐crosslinked decellularized AF hydrogels (g‐DAF‐G) that are injectable and could manifest better in situ formability than noncrosslinked decellularized AF hydrogel, while preserving the capacity of directing differentiation of human bone mesenchymal stem cells (hBMSCs) towards AF cells. Hematoxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…Freeze-drying processes were then performed and the lyophilized decellularized tissues were homogenized into DNP powder or DAF powder. Decellularized matrix hydrogels were prepared as previously described [ 16 ]. Specifically, a certain amount of sterilized DTM powder was added into 0.01 M hydrochloric acid containing pepsin (concentration of pepsin is 1.5 mg/ml) to adjust its concentration to 10 mg/ml.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Freeze-drying processes were then performed and the lyophilized decellularized tissues were homogenized into DNP powder or DAF powder. Decellularized matrix hydrogels were prepared as previously described [ 16 ]. Specifically, a certain amount of sterilized DTM powder was added into 0.01 M hydrochloric acid containing pepsin (concentration of pepsin is 1.5 mg/ml) to adjust its concentration to 10 mg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…All experimental protocols involving human tissue and cells were carried out following The Code of Ethics of the World Medical Association (Declaration of Helsinki) for experiments involving humans and approved by the medical ethics committee of Tongji Medical College of Huazhong University of Science and Technology, and the informed consent of all participating subjects was obtained. As previously described [ 16 ], hBMSCs were extracted from the bone marrow in artificial hip joint replacements. The stemness was evaluated by cellular markers (anti-CD73-APC, anti-CD90-APC, anti-CD105-APC, anti-34-APC, anti-CD45-APC, Biolegend, USA) ( Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in a study comparing the ECM derived from human umbilical cord, crosslinked by genipin and N-(3-Dimethylaminopropyl)-N-ethylcarbodiimide hydrochloride (EDC) for neural tissue application, authors demonstrated that genipin, rather than EDC, improved the bio-stability of injectable ECM hydrogel in biocompatible concentration. 290 In another example, Yizhong Peng et al, 291 established an injectable genipin-crosslinked decellularized annulus fibrosus (dAF) hydrogels and showed that they are better in case of formability, biocompatibility, bioactivity, and mechanical strength in comparison to non-crosslinked dAF.…”
Section: Recellularization Of Cartilagementioning
confidence: 99%
“…In another example, Yizhong Peng et al, 291 established an injectable genipin-crosslinked decellularized annulus fibrosus (dAF) hydrogels and showed that they are better in case of formability, biocompatibility, bioactivity, and mechanical strength in comparison to non-crosslinked dAF.…”
Section: Introductionmentioning
confidence: 99%